Lithium-induced hyperthyroidism in a patient with bipolar type 1 affective disorder: A rare occurrence - Ujjwala Singh; Manish S Nayak; Shreya Singh; Sameer Kumar Praharaj (Apollo Medicine)
A 46-year-old female, previously diagnosed with bipolar affective disorder on lithium therapy, presented to us with manic symptoms. The blood investigations revealed elevated thyroxine and reduced thyroid-stimulating hormone with technetium thyroid scintigraphy indicating lithium-induced thyroiditis.